Memburu Virus Rontokbro dan Variannya - Widodo, Prabowo Pudjo (EXPLORE, 2011)
The fast growth of Rontobro Virus (often referred to as Brontok virus) has infuriated all computer users when the computer works much more slowly than it usually does. The computer is surely infected by viruses, one of which may be the Bronto which has been epidemic on the computer in the recent months. Rontokbro Virus, also referred to as W32IRontokbrogmm has made the operation of the harddisk unstoppable, as seen int the on status of the flickering indicator light indicating that the harddisk is still on in which Rontokbro Virus is reproducing itself. Judging from its name and message, Rontokbro is a domestic virus created by a local Indonesian hacker. This virus has spread all over the world and classified as a second class virus with its separate SMTP (Simple Mail Transfer Protocol). This virus is capable of desimating itself with the multiple messages (mass mailing) dan revoked the idea that local viruses relying on storing media shifting from one computer to another, thus deploying itself in the process. This virus has spread to computer users in enternet-connected Indonesia and South East Asia. Today all internet users in Indonesia and other geographical regions including countries like japan, Spain, Poland, USA, Vietnam, Holland, Sweden, Hungary, Russia, Peru and Israel. The superiority of virus rontokbro is its high capability in social engineering. The attacking techniques of this virus is hyfalsifying the icon (using its own icon folder)as an innocent file, blocking the access to registry editor, Microsoft configuration, command prompt, setting folder setting, folder option, certain security sites and retarting the computer automatically. In order to avoid quick detection by vendor security, this virus can be very selective in sending its own email deliveries